Visualization of Alumni Performance Using Dashboard to Support Higher Education Decision Making - Hesty Ulfatriyani; Eko Prasetyo; Aprilia Kurnianti (Emerging Information Science and Technology, 2020)
Universities in Indonesia create fierce competition. Alumni have an essential role for the educational institution, not only as a tool for measuring the performance quality and ability of education implementation but also as the standard or feedback to the perfection of the education system. One effective data presentation model is the dashboard system seen from the complexity, interactivity, and informative data presented. Therefore, this study aims to build a dashboard system at Universitas Muhammadiyah Yogyakarta (UMY). This study utilized the dashboard life cycle method in its implementation. This method had six stages: project initiation, design, construction, testing, launching and monitoring. This method allowed the study to show data on the number of judicium students, the number of graduates, the average GPA of the alumni, the average study period of alumni, and the number of alumni per graduation level for the 2012/2013 to 2017/2018 academic year, according to the accreditation forms and needs analysis. The dashboard system can provide information about alumni at UMY from 2012 to 2017. The dashboard system is ready to be applied as a decision-making tool, particularly as a strategy for improving the quality and empowering strategy for alumni of the university.